Electronic Surveying: Accuracy of Electronic Positioning Systems - Bigelow, Henry W. (The International Hydrographic Review, 2018)
There are many different electronic systems that can be used for positioning or navigation, on land, at sea, or in the air. Each system differs from the others because each was designed to meet a specific need. There is no one system that meets all needs. The systems may be classified by the kind of line of position generated : hyperbolic, concentric circles, radiais, or composite. The accuracy of position obtained by any one of these systems is a function of two independent terms : repeatability and predictability. Repeatability is the measure of the reliability with which the system permits the user to return to a given spot on the surface of the earth using the electronic lines of position generated by the system. This is what most people mean by “ accuracy ”. It includes the random errors of the system and the effect of the spacing of the lines of position and the angle at which they intersect. The errors of repeatability depend on known quantities. A rapid and reasonably accurate analysis can be made of any proposed installation. The methods of analysis for the different kinds of systems are developed. The predictability of an electronic positioning system is the measure of the reliability with which the system can define the location of a given point in terms of geographic rather than electronic coordinates. I f there is no distortion of the electronic lattice as it is actually propagated, then the position, corrected for errors of repeatability, is the true location. There is always some distortion. The factors causing the distortion are : the conductivity of the surface over which the signal propagates and the refractivity of the atmosphere through which it propagates. These factors are considered in detail, but evaluation is difficult. At present (1963), they can only be derived empirically. A formula for the error of predictability is derived, but it is of little practical use in the present state of the art. Additional study is needed to determine which factors govern the variations in propagation over different kinds of surfaces and the boundaries between them. Knowledge is needed concerning the manner in which the variations in the meteorological conditions of the atmosphere affect the propagation velocity. Techniques must be developed to determine the variation with time and the variation in space of the elements that are found to affect wave propagation. Techniques also are required for the adequate calibration of systems, particularly those with long range.